Translation of Humor Text in German to Indonesian in the Film Subtitle ER IST WIEDER DA - Kartika Dewi Setyaningrum; Rosyidah Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
Translating of humour text in the audiovisual product is an uneasy challenge for the translator. The translator should act as a connector between the original text of the source language (SL) and the audiences of targeted language (TL) to convey the message and information in the film subtitle correctly without eliminating the humorous impact. This study is aimed to identify and describe the translation techniques in the humor text of German film titled Er ist wieder da. The translation is classified by using the techniques offered by Molina and Albir. This is a qualitative study that focuses on translation techniques of the humor text in the subtitle of film Er ist wieder da as the material object of this study. The study found that translator uses 11 techniques that consist of adaptation, borrowing, established equivalent, generalization, linguistic amplification, linguistic compression, literal translation, modulation, particularization, reduction, and transposition.  Keywords: subtitle, humour, translation techniques, Molina and Albir